The Monitoring Method of Enterprise Human Resource Efficiency under the Smart City Management Mode. (31st December 2021) - Ma, Dongjun
Abstract : In order to improve the monitoring effect of corporate human resource efficiency under the smart city management model, this paper establishes an evaluation model for the human resource management model between different growth stages of the organization, different organizations in different industries, and different organizations in the same industry. The proposed human resource management model is based on the deduction result of human resource planning and design, work system design and employee system design, and the dynamic matching of the three. Moreover, this paper uses the three-factor vector evaluation model to modify the management efficiency of the human resource model and designs the corresponding intelligent enterprise human resource efficiency monitoring model. In addition, this paper analyzes the system functions and designs experiments to test the model in this paper. Through experimental testing, it can be seen that the enterprise human resource efficiency monitoring system under the smart city management mode proposed in this paper has good practical results.